LEGAL REVIEW OF THE RESPONSIBILITY OF DOCTORS WHO ACT WITHOUT THE CONSENT OF THE PATIENT'S FAMILY (CASE STUDY OF DECISION NUMBER 3203K/PDT/2017) - Chusmayadi, Omay; Fadhlurrahman Rosyid, Rifqi; Rahman, Alip (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Within the field of medicine, practitioners are guided by teachings on ethics and morals to fulfill their duties and responsibilities in serving the community. Imagine a scenario when a doctor breaches the relevant ethical and moral standards. If such a situation arises, the discipline will be enforced either by the professional association responsible for setting the ethical guidelines or by legal authorities who will process and impose penalties to prevent doctors from neglecting their duty to get informed permission and engaging in malpractice. Informed consent serves a dual purpose for both patients and doctors. For doctors, it provides a sense of assurance when performing medical procedures on patients and acts as a form of protection against potential legal claims or lawsuits that may arise from any unforeseen accidents. Regarding informed consent, it refers to the patient's entitlement to receive comprehensive information regarding their medical condition, the recommended medical procedures, and the potential outcomes associated with each decision.